A Dispositional Theory of Health. (5th February 2018) - Werkhoven, Sander
Abstract: A satisfactory account of the nature of health is important for a wide range of theoretical and practical reasons. No theory offered in the literature thus far has been able to meet all the desiderata for an adequate theory of health. This article introduces a new theory of health, according to which health is best defined in terms of dispositions at the level of the organism as a whole. After outlining the main features of the account and providing formal definitions of 'health', 'healthy', and 'healthier than', I present the main strengths of the proposed account. I argue that the proposed dispositional theory accounts for all paradigm cases of health and pathology, that it circumvents a number of problems faced by rival theories, and that it makes for a naturalistic theory of health with a rigorous metaphysical underpinning. 1 Introduction 2 The Dispositional Account 3 Further Specification of the Dispositional Account 3.1 Reference classes 3.2 Comparison classes 3.3 Which dispositions? 4 Advantages of the Dispositional view 5 Three Objections and Replies 5.1 Objection 1: Counter-examples 5.2 Objection 2: Issues with holism 5.3 Objection 3: Expediting medicalization 6 Final Remarks